Hemostatic Management in Extracorporeal Membrane Oxygenation. Issue 2 (April 2022) - Brokmeier, Hannah M.; Wieruszewski, Erin D.; Nei, Scott D.; Loftsgard, Theodore O.; Wieruszewski, Patrick M.
Abstract : The use of extracorporeal membrane oxygenation (ECMO) for acute cardiac and/or respiratory failure has grown exponentially in the past several decades. Systemic anticoagulation is a fundamental element of caring for ECMO patients. Hemostatic management during ECMO walks a fine line to balance the risk of safe and effective anticoagulant delivery to mitigate thromboembolic complications and minimizing hemorrhagic sequelae. This review discusses the pharmacology, monitoring parameters, and special considerations for anticoagulation in patients requiring ECMO.